Perceções de Ex-Jogadores relativamente à condição de Treinador de Elite - José Diogo Oliveira Miranda (2017)
This dissertation aims to understand the perceptions of the former-player and Football coach about five dimensions of research were outlined: (1) Motivation to exercise the role of coach; (2) The process regarding the transition from being a player to the position of being a coach; (3) Transfer and specific advantages of the player/coach; (4) Game Design; (5) Top-class coach.With the objective of clarifying these issues, 8 coaches with previous experience as professional elite players interviewed, followed by a qualitative analysis of the collected data.The first conclusions led to the identification of a tendency for former players to pursue a coaching career, as a result of their passion for the sport.Non-formal learning through the contact with coaches and observation of coaching techniques throughout their years as players - joined by years of work experience - prove to be deeply fundamental to their own development, without forgetting the importance of the dedicated coaching courses.Despite years of practice as a footballer, along with the associated advantages, this background is not what is generally regarded to be crucial. According to the results obtained, strong leadership, good adaptation capabilities, quality technical knowledge, remarkable decision-making, favorable contexts and exceptional human values are the aspects that define a true elite coach.